2018
DOI: 10.3390/rs10010067
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Evaluation of GNSS-R Based on Future Fully Operational Global Multi-GNSS and Eight-LEO Constellations

Abstract: Spaceborne GNSS-R (global navigation satellite system reflectometry) is an innovative and powerful bistatic radar remote sensing technique that uses specialized GNSS-R instruments on LEO (low Earth orbit) satellites to receive GNSS L-band signals reflected by the Earth's surface. Unlike monostatic radar, the illuminated areas are elliptical regions centered on specular reflection points. Evaluation of the spatiotemporal resolution of the reflections is necessary at the GNSS-R mission design stage for various a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
0
20
1
Order By: Relevance
“…More specifically, the average numbers of points fluctuated around the values of 40, 120, 300, and 600 for the optimal 8-, 24-, 60-, and 120-satellite 2D-LFCs, respectively. What needs to be mentioned is that Gao et al [15] simulated the distribution of the GNSS-R reflection points observed by a LEO constellation with main orbit parameters similar to CYGNSS and found that there is a peak of average numbers of reflection points at 120° E, which was attributed to the denser reflections to BDS GEO and IGSO satellites in the Asia-Pacific region, while in our work, this peak did not exist. This could be due to the fact that both the LEO constellation configurations and the settings for the selection of observable reflections were different between Gao et al's and our studies.…”
Section: The Spatial and Temporal Distributions Of The Reflections Obcontrasting
confidence: 60%
See 4 more Smart Citations
“…More specifically, the average numbers of points fluctuated around the values of 40, 120, 300, and 600 for the optimal 8-, 24-, 60-, and 120-satellite 2D-LFCs, respectively. What needs to be mentioned is that Gao et al [15] simulated the distribution of the GNSS-R reflection points observed by a LEO constellation with main orbit parameters similar to CYGNSS and found that there is a peak of average numbers of reflection points at 120° E, which was attributed to the denser reflections to BDS GEO and IGSO satellites in the Asia-Pacific region, while in our work, this peak did not exist. This could be due to the fact that both the LEO constellation configurations and the settings for the selection of observable reflections were different between Gao et al's and our studies.…”
Section: The Spatial and Temporal Distributions Of The Reflections Obcontrasting
confidence: 60%
“…In the simulation, four steps were followed to determine the available reflected GNSS signals: (1) For each LEO satellite, the potentially available GNSS satellites for reflection observations were selected; (2) The positions of the specular reflection points could be calculated after the positions of the LEO and the GNSS satellites were determined; (3) As shown in Figure 1, only the specular points located within the minimum antenna gain could be contacted; and (4) Furthermore, only the locations of the specular points with 10 highest range corrected gain (RCG) were considered (see the detail of RCG in [16]). In addition, it should be mentioned that the LEO satellites were 3-axis stabilized and the antenna beam widths of the LEO satellites simulated in the present study were the same as that of the TDS-1 satellite, considering that the definitive beam widths of the CYGNSS mission have not been given [15].…”
Section: Simulation Scenariomentioning
confidence: 98%
See 3 more Smart Citations